Family Instrumental Support and Dietary Compliance in Type II Diabetes Mellitus Patients: A Cross-Sectional Study - Fauziansyah, Ahmad; Arifin, Mohammad Fahrul; Pitaloka, Dyah; Miyah, Warti Miftahul (Universitas Pahlawan Tuanku Tambusai, 2025)
Type II Diabetes Mellitus (T2DM) requires strict dietary management to maintain glycemic control. Family instrumental support plays a critical role in patients’ compliance with dietary recommendations, yet the relationship between the two remains underexplored in specific populations. This study investigates the association between family instrumental support and dietary compliance among patients with T2DM. This study employed a non-experimental, observational, analytic design. Sixty-six participants diagnosed with T2DM were recruited using a consecutive sampling technique. This study employed two main instruments: the Family Support Questionnaire and the Dietary Compliance Questionnaire for Type 2 Diabetes. Data were analyzed using Spearman's Rho test to evaluate the correlation between family instrumental support and dietary adherence. Ethical approval for this research was obtained from the Health Research Ethics Committee of the Nahdlatul Ulama Institute of Health Sciences, Tuban, under approval number 347/0084223523/LEPK.IIKNU/XII/2024. The findings indicated that most participants (80.3%) reported receiving strong instrumental support from their families, while 78.5% adhered to dietary recommendations for managing Type 2 Diabetes Mellitus. Among those who received high levels of support, 66.7% demonstrated dietary adherence. Statistical analysis revealed a significant positive correlation between family instrumental support and dietary compliance (p = 0.002; α < 0.05). Instrumental support from family members plays a crucial role in improving dietary adherence among individuals with T2DM. Engagement in routine tasks such as meal preparation and grocery procurement substantially facilitates compliance with medical nutrition therapy and contributes to optimal glycemic regulation.